Treatment of Androgenetic Alopecia Using PRP to Target Dysregulated Mechanisms and Pathways - Abdin, Rama; Zhang, Yusheng; Jimenez, Joaquin J. (Frontiers in Medicine, 2022)
Androgenetic alopecia (“AGA”) is the most prevalent type of progressive hair loss, causing tremendous psychological and social stress in patients. However, AGA treatment remains limited in scope. The pathogenesis of androgenetic alopecia is not completely understood but is known to involve a hair follicle miniaturization process in which terminal hair is transformed into thinner, softer vellus-like hair. This process is related to the dysregulation of the Wnt/β-catenin signaling pathway, which causes premature termination of the anagen growth phase in hair follicles. Historically used for wound healing, platelet rich plasma (“PRP”) has recently been at the forefront of potential AGA treatment. PRP is an autologous preparation of plasma that contains a high number of platelets and their associated growth factors such as EGF, IGF-1, and VEGF. These factors are known to individually play important roles in regulating hair follicle growth. However, the clinical effectiveness of PRP is often difficult to characterize and summarize as there are wide variabilities in the PRP preparation and administration protocols with no consensus on which protocol provides the best results. This study follows the previous review from our group in 2018 by Cervantes et al. to analyze and discuss recent clinical trials using PRP for the treatment of AGA. In contrast to our previous publication, we include recent clinical trials that assessed PRP in combination or in direct comparison with standard of care procedures for AGA such as topical minoxidil and/or oral finasteride. Overall, this study aims to provide an in-depth analysis of PRP in the treatment of AGA based on the evaluation of 17 recent clinical trials published between 2018 and October 2021. By closely examining the methodologies of each clinical trial included in our study, we additionally aim to provide an overall consensus on how PRP can be best utilized for the treatment of AGA.